2011
DOI: 10.1007/s11119-011-9227-4
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of a capacitance probe for measurement and mapping of dry matter yield in Mediterranean pastures

Abstract: The main objective of this study was to calibrate a commercial capacitance probe for measuring pasture dry matter yields under Mediterranean conditions. The standard method of assessing pasture biomass is based on cutting all the forage within a specified area and requires great effort and expense to collect enough samples to accurately represent a pasture. The field tests were carried out in 2007, 2008 and 2009 on different dates (phenological stages), and on five dairy farms, representing typical pastures in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 23 publications
3
30
1
Order By: Relevance
“…Therefore, small solid circular disks of radius a were used as calibration targets. Spherical and disk shapes are not close approximations to the shape of a pasture sward, but the purpose of the laboratory calibration was to confirm the veracity of Equation (7). The size parameter range studied was ka = 1.5−10.4, generally within the geometric scattering range.…”
Section: Calibration In the Laboratorymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, small solid circular disks of radius a were used as calibration targets. Spherical and disk shapes are not close approximations to the shape of a pasture sward, but the purpose of the laboratory calibration was to confirm the veracity of Equation (7). The size parameter range studied was ka = 1.5−10.4, generally within the geometric scattering range.…”
Section: Calibration In the Laboratorymentioning
confidence: 99%
“…Satellite, aerial, and ground-based platforms equipped with advanced sensors provide the potential for fast, non-destructive, and low-cost monitoring of plant growth, development, and yield in a field environment [3]. The methods currently used include the measurement of parameters such as capacitance, spectral properties, pasture height (known as sward height), and compressed sward height [4][5][6][7][8][9][10][11][12]. A wide range of optical sensors have been used to measure a range of parameters of crops and pastures, including biomass [9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews of in situ non-spectral methods pertaining to crops and rangelands can be found in [13][14][15]. These techniques involve: visual assessment (e.g., [16]), crop height (H) (e.g., [17]), fraction of absorbed photosynthetically active radiation (FAPAR) derived from a ceptometer, fraction of vegetation cover (FVC) derived from red-green-blue (RGB) band photographs (e.g., [18]), electronic capacitance probes (e.g., [19]), weighted discs (e.g., [20]) or pendulum sensors (e.g., [21]). …”
Section: Introductionmentioning
confidence: 99%
“…In most trials, pasture growth was determined by Grassmaster II capacitance probe (end measure minus start measure just prior to application). Capacitance probes work by creating an oscillating electric field around the base of the probe; moisture within pasture herbage surrounding the probe modifies the capacitance of this field and the probe estimates the amount of herbage, based on the change in capacitance (see Serrano et al 2011 for further explanation). In one trial, probe data was not collected and mower clipping data was compared instead.…”
Section: Trial Methodologymentioning
confidence: 99%